(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Bacterial infection are difficult to distinguish from viral infection. Neutrophils are the first cells mobilize to infectious site caused by bacteria and also apoptosis of lymphocytes in response to cell mediated immunity hence raised in neutrophils and decrease in lymphocyte count. The goal of this study is to determine the neutrophil to lymphocyte ratio in patient with positive blood culture for bacteria in patients admitted in hospital. Patients and methods: This cross-sectional study was conducted at Department of Pathology, Hamdard University Karachi, Pakistan from 1st January to 31st June 2022. Total 123 adult patients with positive blood cultures admitted in ward or ICU were enrolled in the study. CBC Samples were collected from patients admitted in ward or ICU and blood culture were already sent due to clinical condition, the organism isolated in blood culture were recorded As blood culture is a gold standard investigation to detect bacterial infection .In this study we will record neutrophil to lymphocyte ratio in patients admitted with positive blood culture for bacteria. Age less than 15 years, pregnant female, OPD patients, negative blood cultures and patients on antibiotic therapy were excluded. Complete blood count (CBC) was performed in Beckman coulter model DxH 520 made by Germany. Age and ward of patient, organism isolated from blood culture, CRP. Results: A total of 123 patients with positive blood culture were enrolled in the study. Out of 123 patients 61.8% (n=76) were male and 38.2% (n=47) were female. Mean NLR was 5.9± 13.1. Total 45.5% patients presented with high NLR. Mean CRP was 58.5± 68.7. Conclusion: High NLR was seen in 45.5% which shows NLR is an important indicator of bacterial infection. More studies are needed to define true significance of NLR in all ages and negative blood cultures.